Does BCG vaccine prevent contract and severity of COVID-19 infection in India? A situational analysis - Naik, Bijaya Nanda; Pandey, Sanjay; Singh, Chandra Mani; Ranjan, Alok; Verma, Manisha; Thomas, Ebbie (Indian Journal of Community Health, 2021)
Background: The COVID-19 pandemic has created worldwide emergency with morbidities, mortality and panic. The BCG vaccine, usually given to prevent childhood tuberculosis, surfaced as an option as suggested by some ecological observations. However, some others studies could not establish and explain the protective effects of BCG vaccination against COVID-19 pandemic. India is one country with high BCG vaccination coverage and is among the countries with lowest COVID-19 case fatality rate. Aims and Objectives: We examine the relationship between the BCG coverage and COVID-19 burden in various states/UTs of India. Materials and methods: The information on BCG coverage and morbidity and mortality of COVID-19 was obtained from NFHS and www.covid19India.org respectively. Results: The analysis suggested very weak positive relationship of BCG coverage with cases and deaths due to COVID-19. Moderate positive relationship was observed between BCG coverage and COVID-19 case fatality rate even after adjusting for health system performance. Conclusion: The conclusion of the study is against the role of BCG vaccination in containing the COVID-19 pandemic. The positive correlation which is not significant may be spurious and affected by many confounding factors like co-morbid conditions, testing strategies, population level immunity for other viral infections etc. Hence, the states and UTs should not be complacent by the hypothesized role of BCG vaccine in COVID-19 control. Rather, they should continue with the principles of social distancing, contact tracing, treating and surveillance of COVID-19.